1978
DOI: 10.1007/bf01539634
|View full text |Cite
|
Sign up to set email alerts
|

Handedness in autistics, retardates, and normals of a wide age range

Abstract: Tests of handedness were carried out with 34 autistic children aged from 4 years 10 months to 18 years 11 months, and with sex-, age-, and IQ-matched retardates and sex- and age-matched normals. There were no significant differences between the groups on frequency of handedness, degree of righthand usage, or degree of dominant-hand usage. There was however a significant increase in the variance of dominant-hand usage from normals and retardates to autistics. These results were taken to indicate that earlier re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
5

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 4 publications
1
17
0
5
Order By: Relevance
“…Moreover, it has been found that the proportion of left-handers increases as IQ decreases (Bradshaw-McAnulty et al, 1984;Carlier et al, 2011;Geschwind and Behan, 1982;Gregory and Paul, 1980;Hicks and Barton, 1975;McBurney and Dunn, 1976;Lucas et al, 1989;Pirozzolo and Rayner, 1979;Springer and Eisenson, 1977). By contrast, some studies have failed to report any significant correlation between handedness and IQ (e.g., Annett, 1993b;Barry and James, 1978), while the exact magnitude of the difference in left-handedness between ID individuals and the general population remains under debate.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, it has been found that the proportion of left-handers increases as IQ decreases (Bradshaw-McAnulty et al, 1984;Carlier et al, 2011;Geschwind and Behan, 1982;Gregory and Paul, 1980;Hicks and Barton, 1975;McBurney and Dunn, 1976;Lucas et al, 1989;Pirozzolo and Rayner, 1979;Springer and Eisenson, 1977). By contrast, some studies have failed to report any significant correlation between handedness and IQ (e.g., Annett, 1993b;Barry and James, 1978), while the exact magnitude of the difference in left-handedness between ID individuals and the general population remains under debate.…”
Section: Introductionmentioning
confidence: 86%
“…The studies were coded for classification of handedness using two different groupings: (a) studies with two handedness classes and (b) studies with three handedness classes. In the case of the Barry and James (1978) study where two different cut-off points were used for the determination of the handedness groups, the cut-off points suggested by Annett (1967) were used instead of those suggested by Colby and Parkison, 1997, because Annett uses "more stringent cutoffs for right-and lefthandedness" (Barry and James, 1978, p. 320) and because the classification of Colby and Parkison (1997) "has a number of problems associated with it, not least of which is the arbitrary assignment of a 60% cutoff figure for laterality categorization" (Barry and James, 1978, p. 316).…”
Section: Moderatorsmentioning
confidence: 98%
“…A few investigators, however, did not find such an increase (Barry & James, 1978;Boucher, 1977;Prior & Bradshaw, 1979). Nonetheless, two different hypotheses have been proposed to explain the increased incidence of nonlateralized handedness in autism.…”
mentioning
confidence: 91%
“…Colby and Parkison (1977) suggested that in their study there were more autistics than controls who might have bilateral brain damage early in life that would allow neither cerebral hemisphere to develop dominance. Barry and James (1978) contended that Colby and Parkison's hypothesis was based on a group of very young autistics (i.e., mean age of 4.3 years). They postulated that many of these young autistics were severely retarded in the normal lateralization of cerebral functioning rather than having a failure of normal cerebral lateralization.…”
mentioning
confidence: 98%
“…On the other hand, the fact that they are prone to enjoy music, could be indicative of better development of right hemispheric functions. Barry and James (1978) found that autistic children take more time to develop dominant hand use compared to normals and retarded children, thus indicating delayed cerebral lateralization. In a later paper, James and Barry (1983), pointed out that since development of cerebral dominance is allied to maturity of the CNS, this may be evidence that early onset psychosis is associated with a primary immaturity in CNS organization.…”
Section: Electroencephalogrammentioning
confidence: 94%